2021
DOI: 10.3389/fnins.2021.745815
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Receptor Expressed on Myeloid Cells 2 Protects Dopaminergic Neurons by Promoting Autophagy in the Inflammatory Pathogenesis of Parkinson’s Disease

Abstract: Parkinson’s disease is a neurodegenerative disorder with an inflammatory response as the core pathogenic mechanism. Previous human genetics findings support the view that the loss of TREM2 function will aggravate neurodegeneration, and TREM2 is one of the most highly expressed receptors in microglia. However, the role of TREM2 in the inflammatory mechanism of PD is not clear. In our study, it was found both in vivo and in vitro that the activation of microglia not only promoted the secretion of inflammatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The ratio of LC3‐II/I was more when TREM2 was highly expressed compared to the control group both in vivo and in vitro. This finding suggests that at inflammatory conditions TREM2 boosts autophagy in microglia (Huang et al, 2021).…”
Section: Effects Of Trem2 On Brain Metabolism and Autophagymentioning
confidence: 89%
See 2 more Smart Citations
“…The ratio of LC3‐II/I was more when TREM2 was highly expressed compared to the control group both in vivo and in vitro. This finding suggests that at inflammatory conditions TREM2 boosts autophagy in microglia (Huang et al, 2021).…”
Section: Effects Of Trem2 On Brain Metabolism and Autophagymentioning
confidence: 89%
“…These findings imply that TREM2 keeps microglia in high metabolic states by enhancing mTOR pathway activity, allowing microglia to gather around amyloid plaques in AD models. Studies conducted both in vivo and in vitro suggested that overexpressing TREM2 could inhibit the p38 MAPK pathway as well as the mTOR pathway (Huang et al, 2021). This results in the inhibition of microglial activation and the reduction of damage via inhibiting autophagy in the microglia, demonstrating the anti‐inflammatory and neuroprotective effects of TREM2.…”
Section: Effects Of Trem2 On Brain Metabolism and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…During the experiment, the body weight of the mice in each group was monitored weekly. The pole climbing test, the hanging test, and the rotarod test were used to assess motor coordination and balance in mice …”
Section: Methodsmentioning
confidence: 99%
“…Important role of MAPK signaling in Aβ generation (Du et al, 2019) and cognitive decline independent of amyloid pathology has been proposed in AD (Johnson et al, 2022). Multiple levels of evidence support the TREM2-induced MAPK signaling in PD pathogenesis (Huang et al, 2021;Ruganzu et al, 2022). Microglial MAPK over-activity has been extensively studied in MS (Ten Bosch et al, 2021), while the therapeutic potential of MAPK pathway inhibition in demyelination recovery has also been proposed (Suo et al, 2019).…”
Section: Neuroinflammation Promoting Signaling Pathwaysmentioning
confidence: 99%